UPAYA PENINGKATAN PENGETAHUAN SEPUTAR KANKER PAYUDARA, SADARI UNTUK DETEKSI DINI KANKER PAYUDARA BAGI KARYAWAN UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Ana Majdawati (Universitas Muhammadiyah Mataram, 2021)
Abstrak: Kanker payudara adalah keganasan pada wanita dengan usia diatas 50 tahun yang merupakan dua besar keganasan penyebab kematian. Kanker payudara biasanya ditemukan pada stadium lanjut, karena beberapa penyebab, yaitu pengetahuan yang kurang, rasa malu-takut, pekerjaan yang menyita waktu, kurangnya paparan informasi dari media sosial / elektronik, sosial ekonomi yang tidak memadai, dan lain-lain. Tujuan pengabdian masyarakat ini untuk meningkatkan pengetahuan, keterampilan pemeriksaan payudara sendiri (SADARI) dan mengenalkan pemeriksaan penunjang diagnosis kanker payudara yang penting. Pemeriksaan penunjang diagnosis kanker payudara, yaitu mammografi, ultrasonografi dan Aspirasi Jarum Halus (AJH). Metode pengabdian adalah penyuluhan, brainstorming, dan pelatihan Teknik SADARI melalui workshop dengan alat peraga. Sasaran pengabdian adalah karyawan Universitas Muhammadiyah Yogyakarta (UMY), karena dalam satu tahun terakhir beberapa karyawan UMY terdiagnosis kanker payudara dalam beberapa stadium. Bukti keberhasilan pengabdian adalah peningkatan pengetahuan seputar kanker payudara, dengan perolehan nilai pretest dan post-test rata-rata 65 menjadi 85. Nilai Teknik SADARI sebelum workshop dari 20 peserta yang benar dua orang (10%), dan setelah workshop peserta melakukan dengan benar 100%. Evaluasi lanjut setelah dua hari kegiatan dilaporkan dua orang terdeteksi adanya tumor pada payudara. Abstract: Breast cancer is a malignancy in women over 50 years of age, which are the two most common causes of death. Breast cancer is usually found at an advanced stage, due to several causes, namely inadequate knowledge, timidity, time-consuming work, lack of exposure to information from social / electronic media, inadequate socioeconomic, and others. The aim of this community service is to increase knowledge, skills in breast self-examination (BSE) and introduce important supporting examinations for the diagnosis of breast cancer. Investigations to support the diagnosis of breast cancer include mammography, ultrasound and fine needle aspiration (AJH). The service method is counseling, brainstorming, and BSE technique training through workshops with props. The target of this service is the employees of the Muhammadiyah University of Yogyakarta (UMY), because in the past year several UMY employees were diagnosed with breast cancer in several stages. Evidence of the success of this service is an increase in knowledge about breast cancer, with an average pretest and post-test score of 65 to 85. The BSE technique scores before the workshop were from 20 participants who were right for two people (10%), and after the workshop the participants did it correctly 100 %. A follow-up evaluation after two days of activity reported that two people detected a tumor in the breast.Abstract: Breast cancer is a malignancy in women over 50 years of age, which are the two most common causes of death. Breast cancer is usually found at an advanced stage, due to several causes, namely inadequate knowledge, timidity, time-consuming work, lack of exposure to information from social / electronic media, inadequate socioeconomic, and others. The aim of this community service is to increase knowledge, skills in breast self-examination (BSE) and introduce important supporting examinations for the diagnosis of breast cancer. Investigations to support the diagnosis of breast cancer include mammography, ultrasound and fine needle aspiration (AJH). The service method is counseling, brainstorming, and BSE technique training through workshops with props. The target of this service is the employees of the Muhammadiyah University of Yogyakarta (UMY), because in the past year several UMY employees were diagnosed with breast cancer in several stages. Evidence of the success of this service is an increase in knowledge about breast cancer, with an average pretest and post-test score of 65 to 85. The BSE technique scores before the workshop were from 20 participants who were right for two people (10%), and after the workshop the participants did it correctly 100 %. A follow-up evaluation after two days of activity reported that two people detected a tumor in the breast.